Estudio de prefactibilidad para la instalación de un centro de hemodiálisis sin reuso de dializadores para pacientes diagnosticados con Enfermedad Renal Crónica (ERC) en estadío 5 en la ciudad de Lima - Medina Montes, Mario (2018)
The main objective of this research work is to demonstrate the technical, economic and social feasibility of installing a hemodialysis center without reuse of dialyzers for patients with stage 5 chronic kidney disease in the city of Lima, with the aim of increasing the offer of the service, improve and prolong the quality of life of the patients, as well as improve their employability. The methodology used corresponds to the preparation of a pre-feasibility study, which fundamentally demonstrated the existence of an objective market, it was identified that the optimal location for the installation of the center, the social impact of the project was determined and its economic and financial profitability.